2017
DOI: 10.1192/pb.bp.116.055327
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety and quality of care in mental health: a world of its own?

Abstract: Quality and safety in healthcare, as an academic discipline, has made significant progress over recent decades, and there is now an active and established community of researchers and practitioners. However, work has predominantly focused on physical health, despite broader controversy regarding the attention paid to, and significance attributed to, mental health. Work from both communities is required in order to ensure that quality and safety is actively embedded within mental health research and practice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
0
32
0
1
Order By: Relevance
“…Good practice outlined in the remaining themes broadly applies to all healthcare settings, e.g., ‘developing strong relationships with patients and carers’, and ‘providing timely access to tailored and appropriate care ’ . However, there are important contextual differences in providing safe, high quality care in mental healthcare services, where the majority of patient safety incidents relate to self-harm, aggressive behaviours, restraint, absconding and reduced capacity for self-advocacy [18, 19]. Thus, the consequences of failing to provide good practice in mental healthcare service settings can have serious implications for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Good practice outlined in the remaining themes broadly applies to all healthcare settings, e.g., ‘developing strong relationships with patients and carers’, and ‘providing timely access to tailored and appropriate care ’ . However, there are important contextual differences in providing safe, high quality care in mental healthcare services, where the majority of patient safety incidents relate to self-harm, aggressive behaviours, restraint, absconding and reduced capacity for self-advocacy [18, 19]. Thus, the consequences of failing to provide good practice in mental healthcare service settings can have serious implications for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Questions regarding the status and usefulness of psychiatric diagnosis partly explain this. Uncertainties about the effectiveness of many psychiatric interventions, wide variations in clinical practice, poor patient safety (D'Lima et al ., 2017) and lack of good quality outcome data on matters most relevant to service users (Thornicroft and Slade, 2014) all contribute to the generally negative perceptions of psychiatry. However, the most contentious aspect of contemporary psychiatry is its continuing reliance on coercion as part of clinical care, a legacy of its institutional history.…”
Section: Introductionmentioning
confidence: 99%
“…Many features in guidelines and programs to manage violence are in line with the recovery approach such as involving patients in all decisions about their care and treatment and improving their experience of staying in the ward [19] forming supportive relationships, giving hope, meaningful activities and developing coping skills [13, 20]. This implies that work with safety and quality of care needs to be integrated in order to be beneficial to patients in mental health care [21]. In studies of patient views on psychiatric inpatient wards, patients have reported that they appreciate staff who communicate and create a therapeutic relationship with them.…”
Section: Introductionmentioning
confidence: 99%